PENGEMBANGAN KINERJA PEMASARAN USAHA MEBEL MELALUI INOVASI DAN KETRAMPILAN DI KLATEN - ., Sulistiyani (Proceeding SENDI_U, 2015)
Firm develops some marketing strategy in order to increase the firm profitability and to achieve the properprofitable level. From the previous research, Learning is stated as the newer responsive or better activity, asmatter of fact it is faced by the changing of environment, which eventually the changing itself will determine theinnovation (Daft and Schon, 1978). Marketing performance is the important concept to find out marketachievement of certain product. Performance is defined as the system related to the activity along with theoutcome that achieved. The purpose of this research is to prove whether Learning Orientation, Communicationand Commitment have positive influences toward Performance. This research intends to find out the empiricalevidence which shows Learning Orientation, Communication and Commitment influence to the performance offurniture industry in Klaten Regency. The population on this research is 1802 units of furniture entrepreneurlocated in Klaten Regency, using sample by the means of stratified random sampling for 100-200 units. ( Hairet al, 1995). The analysis method used is confirmatory factor full model of analysis (SEM). From SEM, thecomputation result for the test of significance model is as following: Adjusted Goodness of index (AGFI),Goodness of index (GFI), The Comparative fit index (CFI), Tucker Lewis Index (TLI), Root Mean SquareError of Approximation (RMSEA) and Critial Ratio (CR). The result of this research shows that the model onthis research meets with the goodness of fit criteria and Regression Weight requirements. (Chisqure=87,653,probability=0,088, AGFI=0,843, GFI=0,894, CFI=0,981, TLI=0,976, RMSEA=0,049). Thus, LearningOrientation, Working Motivation and Commitment have positive influence toward the performance of furnitureentrepreneur in Klaten Regency.Key Words : learning orientation,skill , comunication, performance